Maintaining the Quality of the Institution by Implementing the Education Services Mix - Eneng Siti Suherni; Achmad Wahyudin; Abdul Mu’in (PT FORMOSA CENDEKIA GLOBAL, 2023)
Nowadays, the challenges for educational institutions are starting to increase in competition, so that there are many educational institutions offering services. An educational institution must be able to maintain quality so as to market the institution, maintain the value of its existence or existence. Various interesting events occur when implementing education, when accepting new prospective students, people are now starting to be smart in choosing educational institutions for their sons/daughters. The institution must have a good image in view. To create a brand image for educational institutions, an appropriate marketing strategy for educational services is needed, namely the 7P marketing theory. The elements of the educational services marketing mix consist of seven educational services marketing tools, which are also known as 7p; Product, Price, Place, Promotion, People, Physical Evidence, Process, Field of analysis; school environment, school products and services, customers or stakeholders, and school competitors. School competitive strategy; 1. Reduction of education costs, 2. Quality of education. 3. Educational innovation strategy.